In vivo activation of the hypoxia-targeted cytotoxin AQ4N in human tumor xenografts - Williams, Kaye J.; Albertella, Mark R.; Fitzpatrick, Brian; Loadman, Paul M.; Shnyder, Steven D.; Chinje, Edwin C.; Telfer, Brian A.; Dunk, Chris R.; Harris, Peter A.; Stratford, Ian J. (Molecular cancer therapeutics, 2009)
AQ4N (banoxantrone) is a prodrug that, under hypoxic conditions, is enzymatically converted to a cytotoxic DNA-binding agent, AQ4. Incorporation of AQ4N into conventional chemoradiation protocols therefore targets both oxygenated and hypoxic regions of tumors, and potentially will increase the effectiveness of therapy. This current pharmacodynamic and efficacy study was designed to quantify tumor exposure to AQ4 following treatment with AQ4N, and to relate exposure to outcome of treatment. A single dose of 60 mg/kg AQ4N enhanced the response of RT112 (bladder) and Calu-6 (lung) xenografts to treatment with cisplatin and radiation therapy. AQ4N was also given to separate cohorts of tumor-bearing mice 24 hours before tumor excision for subsequent analysis of metabolite levels. AQ4 was detected by high performance liquid chromatography/mass spectrometry in all treated samples of RT112 and Calu-6 tumors at mean concentrations of 0.23 and 1.07 μg/g, respectively. These concentrations are comparable with those shown to be cytotoxic in vitro . AQ4-related nuclear fluorescence was observed in all treated tumors by confocal microscopy, which correlated with the high performance liquid chromatography/mass spectrometry data. The presence of the hypoxic marker Glut-1 was shown by immunohistochemistry in both Calu-6 tumors and RT112 tumors, and colocalization of AQ4 fluorescence and Glut-1 staining strongly suggested that AQ4N was activated in these putatively hypoxic areas. This is the first demonstration that AQ4N will increase the efficacy of chemoradiotherapy in preclinical models; the intratumoral levels of AQ4 found in this study are comparable with tumor AQ4 levels found in a recent phase I clinical study, which suggests that these levels could be potentially therapeutic. [Mol Cancer Ther 2009;8(12):3266–75]